Nanostructured lipid carriers for incorporation of copper(II) complexes to be used against Mycobacterium tuberculosis - Sato, Mariana R. [UNESP]; Oshiro Junior, João A. [UNESP]; Machado, Rachel T. A. [UNESP]; de Souza, Paula C. [UNESP]; Campos, Débora L. [UNESP]; Pavan, Fernando R. [UNESP]; da Silva, Patricia B. [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2017)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. Cessation of treatment before the recommended conclusion may lead to the emergence of multidrug-resistant strains. The aim of this study was to develop nanostructured lipid carriers (NLCs) for use in the treatment of M. tuberculosis. The NLCs comprised the following lipid phase: 2.07% polyoxyethylene 40 stearate, 2.05% caprylic/capric triglyceride, and 0.88% polyoxyl 40 hydrogenated castor oil; the following aqueous phase: 3.50% poloxamer 407 (F1–F6), and 0.50% cetyltrimethylammonium bromide (F7–F12); and incorporated the copper(II) complexes [CuCl2(INH)2]⋅H2O (1), [Cu(NCS)2(INH)2]⋅5H2O (2), and [Cu(NCO)2(INH)2]⋅4H2O (3) to form compounds F11.1, F11.2, and F11.3, respectively. The mean diameter of F11, F11.1, F11.2, and F11.3 ranged from 111.27±21.86 to 134.25±22.72 nm, 90.27±12.97 to 116.46±9.17 nm, 112.4±10.22 to 149.3±15.82 nm, and 78.65±6.00 to 122.00±8.70 nm, respectively. The polydispersity index values for the NLCs ranged from 0.13±0.01 to 0.30±0.09. The NLCs showed significant changes in zeta potential, except for F11.2, with F11, F11.1, F11.2, and F11.3 ranging from 18.87±4.04 to 23.25±1.13 mV, 17.03±1.77 to 21.42±1.87 mV, 20.51±1.88 to 22.60±3.44 mV, and 17.80±1.96 to 25.25±7.78 mV, respectively. Atomic force microscopy confirmed the formation of nanoscale spherical particle dispersions by the NLCs. Differential scanning calorimetry determined the melting points of the constituents of the NLCs. The in vitro activity of copper(II) complex-loaded NLCs against M. tuberculosis H37Rv showed an improvement in the anti-TB activity of 55.4, 27.1, and 41.1 times the activity for complexes 1, 2, and 3, respectively. An in vivo acute toxicity study of complex-loaded NLCs demonstrated their reduced toxicity. The results suggest that NLCs may be a powerful tool to optimize the activity of copper(II) complexes against M. tuberculosis.
Keywords: Copper(II) complex; In vitro activity; In vivo acute toxicity assay; M. tuberculosis; Nanostructured lipid carriers; Tuberculosis